Propriedades ópticas não lineares de compostos orgânicos : chalconas e corantes de oxazóis - Abegão, Luis Miguel Gomes (2017)
The most recent developments in the field of nonlinear optics (NLO) show that organic molecules with electron donating or accepting substituents at either ends of a long -conjugation could be promising candidates for integration into photonic devices or applications such 3D microfabrication, optical-limiting, photodynamic therapy, biological probes, etc. Linear and nonlinear optical measurements were carried out for two classes of organic molecules: chalcones and oxazoles. Second- and third-order nonlinear optical properties, namely the first molecular hyperpolarizability ( HRS) and the cross-section of two-photon absorption ( A2F ), respectively, were measured for eight chalcones and for six oxazoles dyes. The experimental values of HRS and A2F were achieved by using hyper-Rayleigh Scattering and Z-Scan techniques, respectively. HRS maximum values of 42 10-30 (esu) and 412 10-30 (esu), for chalcones and oxazoles compounds, respectively, have been obtained. The A2F maximum values of 42 GM and 85 GM for chalcones and oxazoles compounds, respectively, have been obtained. This study has identified the lower performance of chalcones compared to the oxazoles compounds for both NLO effects studied, probably due to the length difference in the -conjugation together with the different electron donor groups present in both compounds. Whenever possible, and in order to better understand the experimental results, quantum chemical calculations were performed employing density-functional theory using the Dalton and Gaussian software.